From the Written to the Enacted Curricula: The Intermediary Role of Middle School Mathematics Teachers in Shaping Students' Opportunity to Learn - Tarr, James E.,; Chávez, Óscar,; Reys, Robert E.; Reys, Barbara J. (School Science and Mathematics, 2006)
In this paper is reported the extent of textbook use by 39 middle school mathematics teachers in six states, 17 utilizing a textbook series developed with funding from the National Science Foundation (NSF-funded) and 22 using textbooks developed by commercial publishers (publisher-generated). Results indicate that both sets of teachers placed significantly higher emphasis on Number and Operation, often at the expense of other content strands. Location of topics within a textbook represented an oversimplified explanation of what mathematics gets taught or omitted. Most teachers using an NSF-funded curriculum taught content intended for students in a different (lower) grade, and both sets of teachers supplemented with skill-building and “practice” worksheets. Implications for documenting teachers' “fidelity of implementation” (National Research Council, 2004) are offered.